2001
DOI: 10.1645/0022-3395(2001)087[0923:boanfi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Atrial Natriuretic Factor in an Experimental Model of Trypanosoma cruzi Infection in Rats

Abstract: Enhanced atrial natriuretic factor (ANF) production by the heart is related to hemodynamic overload, cardiac growth, and hypertrophy. The heart is one of the most affected organs during Trypanosoma cruzi infection. We tested the hypothesis that myocarditis produced by parasite infection alters the natriuretic peptide system by investigating the behavior of plasma ANF during the acute and chronic stages of T. cruzi infection in rats. Sprague-Dawley rats were infected with T. cruzi clone Sylvio-X10/7. Cardiac mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Natriuretic peptides have been shown to be involved in the pathogenesis of Chagas disease in animal experiments [23], [24] and some clinical studies have reported that BNP levels are increased in Chagas cardiomyopathy [25], [26], [27] and correlates with prognosis [28]. Ribeiro et al demonstrated a high specificity with moderate sensitivity for BNP to detect LVEF≤40% in infected patients with an abnormal ECG or chest X-ray [25].…”
Section: Discussionmentioning
confidence: 99%
“…Natriuretic peptides have been shown to be involved in the pathogenesis of Chagas disease in animal experiments [23], [24] and some clinical studies have reported that BNP levels are increased in Chagas cardiomyopathy [25], [26], [27] and correlates with prognosis [28]. Ribeiro et al demonstrated a high specificity with moderate sensitivity for BNP to detect LVEF≤40% in infected patients with an abnormal ECG or chest X-ray [25].…”
Section: Discussionmentioning
confidence: 99%
“…Natriuretic peptides (brain and atrial) were among the first markers of cardiac disease progression ever considered. These are released under conditions of myocardial stress and have been shown to be increased in T. cruzi experimentally infected animals (21), and in Chagas disease patients with cardiomyopathy (22). Furthermore, levels of natriuretic peptides correlated to clinical prognosis (23).…”
Section: Biochemical Markers Of Disease Progressionmentioning
confidence: 99%